RAGAM REPRESENTASI IKLAN SENSUAL DI TELEVISI (KAJIAN SEMIOTIKA ROLAND BARTHES) - Ratu Nadya Wahyuningratna; Windhi Tia Saputra (Dialektika, 2018)
Electronic media has become a media that is effective enough to educate and provide information to the public, but if it is misused this medium can be a powerful medium to spread negative messages. The influence of television shows will be seen after the public receives messages from television. Today there are various types of shows on television but not all types of impressions have a good effect on the audience. There are several types of television shows that actually cause concern in the community because of wrong perceptions captured from television shows. For example, the existence of ad impressions that indulge the sensuality of women in the storyline. In this case, the advertisements in question are "Mana Tahan" version of Mie Sedaap ad, Sutra Condom advertisement version "Enaknya Sama-sama", and "Zaskia Gothic" version of the Kyoto Bed Sheet ad. These advertisements began airing in 2017 and we can still see them on television. The purpose of this study was to determine the connotation and denotation meanings and some myths in these advertisements which were considered to represent sensuality. This study uses a qualitative research approach with semiotic analysis methods. The subjects in this study were advertisements for Sutra Condoms, Mie Sedaap and Kyoto Bed Sheet on television which would be the subject of analysis. The results of this study are expected to be followed up by advertisers in producing communication messages in advertisements with the suitability of national discourse/values circulating in the community in their works, so that the advertising climate in the country can be better.